Escola politécnica e suas múltiplas relações com a cidade de São Paulo 1893-1933 - Souza, Ana Cláudia Ribeiro de (2006)
Based on the discussion about professional education, the laboratories, railroads and the polytechnicians action, this work investigated the relations between the Polytechnic School and the city of São Paulo, in the period between 1893 and 1933. A vast amount of documents were used in this study and correlations were established between them, highlighting Revista Politécnica (Polytechnic Journal) as one of the elements that contributed to the formation of the professional class of the engineer. The work discusses the Polytechnic School as a space of the rationality that was established in São Paulo at the beginning of the Republic, connected with a macro political project of São Paulo s Republican Party, in a correlation between education and politics in the discussion about the implementation of the liberal model in São Paulo and the legislative consequences that derived from it. During this period, the Polytechnic School of São Paulo became one of the historical subjects that constructed the conception of engineering in Brazil. Engineering is understood here as the art of making and transforming nature in favor of man s welfare